The time squares sequences: a new task for assessing visuospatial working memory - Mirino, Pierandrea; Mercuri, Sara; Pecchinenda, Anna; Boccia, Maddalena; Di Piero, Andrea; Soldani, Marta; Guariglia, Cecilia (Frontiers in Behavioral Neuroscience, 2023)
Several studies have shown that working memory is sensitive to temporal variations. We used a new visuospatial working memory task – the "Time Squares Sequences" -- to investigate whether implicit variations in stimuli presentation time affect task performance. Fifty healthy participants saw two sequences (S1 and S2) of 7 white squares presented in a matrix of grey squares and assessed whether S2 matched S1. There were four conditions depending on the spatial position and the presentation time (i.e., timing) of the white squares in S1 and S2: two with same (S1 fixed/S2 fixed; S1variable/S2 variable) and two with different (S1 fixed/S2 variable; S1 variable/S2 fixed) presentation time. Findings showed impaired performance when S1 had fixed presentation time and S2 had a variable presentation time. These findings are attributed to increased cognitive load due to S2 timing difference, pointing to a monitoring process, sensitive to temporal variations.